2021
DOI: 10.1111/1749-4877.12579
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal pattern of the thermal sensitivity of running speed in the endemic lizard Liolaemus multimaculatus

Abstract: Physiological performance in lizards may be affected by climate across latitudinal or altitudinal gradients. In the coastal dune barriers in central‐eastern Argentina, the annual maximum environmental temperature decreases up to 2°C from low to high latitudes, while the mean relative humidity of the air decreases from 50% to 25%. Liolaemus multimaculatus, a lizard in the family Liolaemidae, is restricted to these coastal dunes. We investigated the locomotor performance of the species at 6 different sites distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 106 publications
(330 reference statements)
0
8
1
Order By: Relevance
“…Furthermore, a similar T o (∼34°C) was estimated in other populations of L. elongatus (Bonino, Moreno Azócar, Schulte, Abdala, et al, 2015; Moreno Azócar et al, 2020). This result contrasts with the findings for other species of Liolaemus such as L. multimaculatus , from the coast of Argentina, which show a decrease in the T o in six populations along a latitudinal gradient (Stellatelli et al, 2021).…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, a similar T o (∼34°C) was estimated in other populations of L. elongatus (Bonino, Moreno Azócar, Schulte, Abdala, et al, 2015; Moreno Azócar et al, 2020). This result contrasts with the findings for other species of Liolaemus such as L. multimaculatus , from the coast of Argentina, which show a decrease in the T o in six populations along a latitudinal gradient (Stellatelli et al, 2021).…”
Section: Discussioncontrasting
confidence: 86%
“…Comparison of means or medians of maximum locomotor speeds (V max i ) of each temperature trial (20°C or 30°C) between the group acclimated at low temperature (22°C) and the group acclimated at high temperature (30°C). Argentina, which show a decrease in the T o in six populations along a latitudinal gradient (Stellatelli et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, although its thermal safety margin is currently narrow, we believe it will be capable of coping with global warming given that it has great amplitude of thermal performance together with its strategy of thermoregulation. However, studies which analyse other populations within its range of distribution are necessary, as interpopulation variations in thermoregulation behaviour (Artacho et al, 2017) and locomotor performance (Cecchetto et al, 2020; Stellatelli et al, 2021) have been reported for other species of lizards. Degrees of acclimatization (Kubisch et al, 2016) and the way in which species use thermal shelters (Vicenzi, Ibargüengoytía et al, 2019) have also been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Body size is a key life-history trait [ 33 , 34 , 35 , 36 , 37 ] that is affected by some factors, including resource consumption, interactions, population dynamics and community assembly in different environments [ 38 , 39 , 40 , 41 ]. Thus, body size should be associated with metabolic rate, population density, longevity, and geographic range (see [ 38 , 42 , 43 ]). Identifying the environmental factors that affect body size variation among populations is important in order to understand how animals adapt to abiotic environments by changing their phenotypic plasticity [ 22 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%